Keep God’s Commandments and Words to Bear Fruits - Nguyen, Minh Doan (Khoa Học Công Giáo và Đời Sống, 2021)
Remaining in God’s love is the main topic of John 15. To remain in God, we must keep His commandments and abide in His words. And the result of this relationship – the measure to find out Jesus in us - is we bear fruits. Let’s consider them deeply.